On “Savage and Deformed Slave”: Bodily Difference in Selected Contemporary Productions of The Tempest in Poland - Kowalcze-Pawlik, Anna (Romanica Silesiana, 2021)
Dis/ability is a dynamic category produced in a complex constellation of factors that includes not only stigmatised mental and physical constraints or physiological differences, but also a manifestation of incapacity that is recognised or produced by law, social norms and the very way of thinking about the nature of bodily vulnerability. The meanings of dis/ability are thus culturally and historically dependent. Therefore, the manner in which dis/ability is presented on a theatrical stage can be considered not only as an important factor influencing the interpretation of a given production but also as a test for the dominant thinking of disability at a given point of time, in a given culture. The departure point for this paper is a brief discussion of the visibility of medieval models of dis/ability in Shakespeare’s plays and a reflection on how the reception of these dramatic texts has changed over time depending on the paradigmatic shifts in thinking about dis/ability, especially with the emergence of disability studies and the growing theoretical reflection on the position of dis/ability in theatre. An especially interesting case in point is the reception of Caliban as a character whose stigmatisation can be expressed through bodily difference. Thus, the paper focuses on what seems to be a systematic aberrant decoding of The Tempest in three twenty-first century Polish productions of the play.